h - Campos, Pedro; Graham, Nicholas; Jorge, Joaquim; Nunes, Nuno.; Palanque, Philippe; Winckler, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The four-volume set LNCS 6946-6949 constitutes the refereed proceedings of the 13th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2011, held in Lisbon, Portugal, in September 2011. ((Text folgt)) The fourth volume includes 27 regular papers organized in topical sections on usable privacy and security, user experience, user modelling, visualization, and Web interaction, 5 demo papers, 17 doctoral consortium papers, 4 industrial papers, 54 interactive posters, 5 organization overviews, 2 panels, 3 contributions on special interest groups, 11 tutorials, and 16 workshop papers.
Keywords: Computer science; Software engineering; Information systems; Artificial intelligence; Education; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computers and Education; Computers and Society; Software Engineering